Optic Neuropathy and Macular Ischemia Associated with Neurosarcoidosis: A Case Report - Burak Tanyıldız; Gizem Doğan; Nilüfer Zorlutuna Kaymak; Mehmet Engin Tezcan; Ahmet Kasım Kılıç; Sevda Şener Cömert; Aysu Karatay Arsan (Türk Oftalmoloji Dergisi, 2018)

(untitled)
In this study, we present a case of bilateral optic neuropathy and macular ischemia in the right eye associated with neurosarcoidosis. A 26-year-old woman presented to our clinic with complaints of bilateral blurred vision. Bilateral granulomatous anterior uveitis, vitritis, optic neuropathy, and macular ischemia were detected in the right eye in slit-lamp examination. She also reported complaints of fever, weakness, sweating, arthralgia, and headache for 2 months. She was referred to the pulmonary diseases unit of our hospital due to hilar lymphadenopathy seen in her chest x-ray, and biopsies were taken for diagnostic purposes. Histological analysis of the mediastinal lymph node biopsies revealed chronic, non-caseating, granulomatous inflammation. Furthermore, the patient was referred to a neurologist due to concomitant complaint of intense headaches. She was diagnosed with neurosarcoidosis supported by findings on cranial magnetic resonance imaging and lumbar puncture. She received a 3-day course of high-dose (1 g/day) intravenous steroid treatment (methylprednisolone) followed by a tapering dose of oral prednisone. The patient began receiving oral methotrexate 15 mg/week as a steroid-sparing agent. Significant improvement in neurological and ophthalmological symptoms occurred in the first week of treatment. In this case report, we emphasized that neurosarcoidosis should be included in the differential diagnosis of patients with both bilateral optic neuropathy and macular ischemia. Furthermore, early diagnosis and timely treatment of neurosarcoidosis are important for favorable visual outcomes.